Hepatoprotective and nephroprotective efficacy of Cichorium intybus following imidacloprid induced subchronic toxicity in WLH cockerels - Deeksha Maletha; Satya Pal Singh; S RAMANARAYANAN (The Indian Journal of Animal Sciences, 2022)
The current research work was undertaken to evaluate the hepatoprotective and nephroprotective potential of Cichorium intybus following subchronic exposure of imidacloprid in white leghorn (WLH) chicks. Thirty, 6 to 8 weeks old chicks of 300-350 g weight were randomly and equally divided into five groups. Group I served as control and was fed normal grower ration and other were fed medicated ration containing Cichorium intybus leaf powder @ 5000 ppm in Group II, imidacloprid @ 100 ppm in Group III, imidacloprid @ 100 ppm + silymarin @ 100 ppm in Group IV and imidacloprid @ 100 ppm + Cichorium intybus leaf powder @ 5000 ppm in Group V, respectively, for 8 weeks. Biochemical parameters at 4th and 8th week revealed a significant increase in alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, γ-glutamyl transferase, lactate dehydrogenase, total bilirubin, indirect bilirubin, creatinine, blood urea nitrogen (BUN) with an increase in absolute and relative organ weights of liver and kidney after 8 weeks and a significant decline in total protein, albumin and globulin in imidacloprid treated Group III as compared to control (Group I). However, the simultaneous administration of Cichorium intybus leaf powder (CILP) in Group V revealed amelioration in these parameters at par with Groups I and IV. Thus, amelioration of imidacloprid induced hepatotoxic and nephrotoxic effects following simultaneous CILP administration indicates hepatoprotective and nephroprotective potential of Cichorium intybus in imidacloprid intoxicated cockerels.